Prediksi Harga Saham Menggunakan Model Valuasi Teori Surplus Bersih Berdasarkan Pendekatan Ohlson - Sarah Yuliarini (AKRUAL: JURNAL AKUNTANSI, 2010)
AbstractThe aim of empirical research is continouing study about clean-surplus theory contributed to valuing firm that listed  in Indonesian capital marked. Ohlson (1995) had resolved final counts by assuming that abnormal earning have a regressing time could be counted based on accounting data. The result have to be correlated with marked capitalized. Regression tested refer to positive correlation and significant with marked valued. Valuation adopted Ohlson (1995) count about 130%, when it could be in post of global monetary crisis, above of marked value differ with prior result. In summary, Ohlson model valuation can be adopted in Indonesia confidently.